2012
DOI: 10.1111/j.1570-7458.2012.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in frequencies of genes that enable Phyllotreta nemorum to utilize its host plant, Barbarea vulgaris, vary in magnitude and direction, as much within as between seasons

Abstract: The interaction between the flea beetle, Phyllotreta nemorum L. (Coleoptera: Chrysomelidae), and its host plants is well suited to study the dynamics of a geographic mosaic of (co)evolution. The flea beetle can either be resistant or susceptible to the defense of one of its host plants, Barbarea vulgaris R.Br. G‐type (Brassicaceae). Previous findings suggested that the frequency of resistant beetles on host plants other than the G‐type of B. vulgaris had decreased over time within the period of 1999–2003. In 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…If as expected, coevolutionary interactions are both spatially and temporally dynamic (Torres, ) and are important for biological control services (Holt & Hochberg, ; Jones et al., ; Kraaijeveld & Godfray, , ), then localized breakdowns in biological control services might be a common and transitory occurrence as predicted by the geographic mosaic theory of coevolution (Thompson, , ). While geographic mosaics have been observed for interactions between herbivores and plants (Muola et al., ; Siepielski & Benkman, ; Vermeer, Verbaarschot, & de Jong, ), predators and prey (Brodie & Ridenhour, ), and hosts and parasites (Dixon, Craig, & Itami, ; Lorenzi & Thompson, ; Thompson, ; Vergara, Lively, King, & Jokela, ), as of yet there are no known documented examples from the biological control literature. It has been proposed, however, that a geographic mosaic of coevolution may have played an important role in the establishment of invasive knapweeds ( Centaurea maculosa Lamarck and C. diffusa Lamarck) in North America (Callaway, Hierro, & Thorpe, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If as expected, coevolutionary interactions are both spatially and temporally dynamic (Torres, ) and are important for biological control services (Holt & Hochberg, ; Jones et al., ; Kraaijeveld & Godfray, , ), then localized breakdowns in biological control services might be a common and transitory occurrence as predicted by the geographic mosaic theory of coevolution (Thompson, , ). While geographic mosaics have been observed for interactions between herbivores and plants (Muola et al., ; Siepielski & Benkman, ; Vermeer, Verbaarschot, & de Jong, ), predators and prey (Brodie & Ridenhour, ), and hosts and parasites (Dixon, Craig, & Itami, ; Lorenzi & Thompson, ; Thompson, ; Vergara, Lively, King, & Jokela, ), as of yet there are no known documented examples from the biological control literature. It has been proposed, however, that a geographic mosaic of coevolution may have played an important role in the establishment of invasive knapweeds ( Centaurea maculosa Lamarck and C. diffusa Lamarck) in North America (Callaway, Hierro, & Thorpe, ).…”
Section: Discussionmentioning
confidence: 99%
“…If as expected, coevolutionary interactions are both spatially and temporally dynamic (Torres, 2009) and are important for biological control services (Holt & Hochberg, 1997;Jones et al, 2014;Kraaijeveld & Godfray, 1999, then localized breakdowns in biological control services might be a common and transitory occurrence as predicted by the geographic mosaic theory of coevolution (Thompson, 1994(Thompson, , 2005. While geographic mosaics have been observed for interactions between herbivores and plants (Muola et al, 2010;Siepielski & Benkman, 2005;Vermeer, Verbaarschot, & de Jong, 2012), predators and prey (Brodie & Ridenhour, 2002), and hosts and parasites (Dixon, Craig, & Itami, 2009;Lorenzi & Thompson, 2011;Thompson, 2009b This is in part due to the fact that there have been very few longterm, postrelease studies of biological control agents and their targets (McCoy & Frank, 2010;Mills, 2000Mills, , 2017, and that it can be difficult to identify a priori which adaptive traits to measure when studying coevolutionary interactions. In this context, comparative population genomics may provide a useful approach to obtain preliminary evidence for the presence and/or potential importance of coevolution in biological control systems.…”
Section: Geographic Mosaic Of Coevolutionmentioning
confidence: 99%
“…Although the saponin-based defence of B.vulgaris is a dead-end for most Ph.nemorum genotypes, resistant individuals that performed well on the G-type were found at varying frequencies in all sampled populations (Nielsen and de Jong 2005; Nielsen 2012; Vermeer et al 2012). The ability to use the G-type as a host plant clearly shows that resistant individuals can tolerate or detoxify saponins by an unknown mechanism.…”
Section: Adaptations Of Crucifer-feeding Flea Beetles To Chemical Plamentioning
confidence: 99%
“…However, it showed that the presence or absence of leaf pubescence in B. vulgaris var. arcuata seemed to be correlated with many chemical and biological features (Agerbirk et al, 2001;Vermeer et al, 2012;de Jong and Nielsen, 2013), which differed significantly between the two types. It's suggested a greater taxonomic distance between the two types of B. vulgaris var.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%